Multiple Magnetic Phases in Van Der Waals Mn‐Doped SnS2 Semiconductor. (2nd May 2021) - Bouzid, Houcine; Sahoo, Ramchandra; Yun, Seok Joon; Singh, Kirandeep; Jin, Youngjo; Jiang, Jinbao; Yoon, Duhee; Song, Hyun Yong; Kim, Giheon; Choi, Wooseon; Kim, Young‐Min; Lee, Young Hee
Abstract: 2D van der Waals magnetic semiconductors have emerged along with the possibilities of achieving an efficient gate tunability and a proximity effect with a high magnetic anisotropy compared with 3D counterparts. Little explored are multiple magnetic phases with a single crystallographic phase. Herein, the multiple magnetic phases in a Mn‐doped SnS2 single crystal with different doping concentrations using a one‐step self‐flux method are reported. Two ferromagnetic phases with a canted spin direction exist regardless of the Mn‐doping concentration at up to 5 at%. Antiferromagnetism coexists with the ferromagnetic order and strengthens at high Mn‐doping concentrations. A magnetoresistance measurement conducted on a 2 at% Mn‐SnS2 flake exhibits a positive‐to‐negative crossover with a value of as high as 50% and clear anisotropy, confirming the presence of ferromagnetic order in the material. By revealing multiple magnetic phases in Mn‐doped SnS2, the study broadens the scope of state‐of‐the‐art research on layered magnetic semiconductors. Abstract : Multiple magnetic phases emerge in single‐crystal SnS2 layered semiconductors. Two ferromagnetic (FM) transitions with Curie temperatures dependent on Mn‐doping concentration can be distinguished based on magnetic measurements. The positive‐to‐negative crossover and anisotropy in magnetoresistance further confirm the FM semiconducting behavior. Mn‐SnS2 is expected to enlarge the scope of layered FM semiconductors towards practical applications in the field of spintronics.